Epigenome-wide association study of biomarkers of liver function identifies albumin-associated DNA methylation sites among male veterans with HIV - Titanji, Boghuma K.; Lee, Mitch; Wang, Zeyuan; Chen, Junyu; Hui, Qin; Lo Re III, Vincent; So-Armah, Kaku; Justice, Amy C.; Xu, Ke; Freiberg, Matthew; Gwinn, Marta; Marconi, Vincent C.; et al. (Frontiers in Genetics, 2022)
Graphical Abstract